(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The discovery of ammonoids at the top of the Cunardo Formation allows the revision of the chronostratigraphic position of the unit. Detoniceras, Argolites and Anolcites testify the Archelaus Zone. The age of the unit is then Ladinian instead of Carnian, as reported in literature.